2016
DOI: 10.1111/gcbb.12400
|View full text |Cite
|
Sign up to set email alerts
|

The expansion of short rotation forestry: characterization of determinants with an agent‐based land use model

Abstract: Wood is a limited resource which is exposed to a continuously growing global demand not least because of a politically fostered bioenergy use. One approach to master the challenge to sustainably meet this increasing wood demand is short rotation forestry (SRF). However, SRF is only gradually evolving and it is not fully understood which determinants hamper its expansion. This study provides theoretical insights into economic and environmental determinants of an SRF expansion and their interplay. This assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
0
14
0
1
Order By: Relevance
“…Although this study focused on SRP on marginal land, we found that in many cases the barriers and incentives indentified for SRP on regular agricultural land were also true for marginal land such as the competition of SRP with other agricultural production and expected negative impacts on soil [21,39,43,45]. Interestingly, these two main benefits commonly communicated to support SRP on marginal soil were not perceived by all farmers.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Although this study focused on SRP on marginal land, we found that in many cases the barriers and incentives indentified for SRP on regular agricultural land were also true for marginal land such as the competition of SRP with other agricultural production and expected negative impacts on soil [21,39,43,45]. Interestingly, these two main benefits commonly communicated to support SRP on marginal soil were not perceived by all farmers.…”
Section: Discussionmentioning
confidence: 85%
“…With regard to financial barriers, SRP can provide access to attractive new markets (e.g., energy, material use). Literature argues that SRP yields are not yet economically viable as a result of high investment costs [26] combined with uncertain returns on investment due to price volatility [43].…”
Section: Incentives and Barriers Relevant To The Adoption Of Srpmentioning
confidence: 99%
“…Falconer et al [55] and Nouri et al [56] asserted that policy recommendations generated by top-down modeling methods may not be effective, because they fail to account for agents' behavioral norms and potential changes in behavior in responses to interventions. As pointed out by Schulze et al [57] and Bieber et al [10], many FEWS policy questions focus on introducing or expanding a production activity for which few or no studies exist, and the agent-based approach enables exploration of these activities by simulating decision-making processes and their implications under different or hypothetical conditions. Similarly, Holtz and Pahl-Wostl [58] emphasized the process-based nature of ABMs as an advantage, which enables causal connects between changing conditions and behavioral responses and/or system transitions.…”
Section: Justifications For Using Abmmentioning
confidence: 99%
“…Apesar de representar um recurso com efeitos positivos nos domínios da bioeconomia, biodiversidade e preservação da qualidade dos solos, o desenvolvimento de culturas de floresta dedicadas a fins energéticos na União Europeia tem tido uma expansão bastante lenta, ao contrário do que está a acontecer ao nível internacional (Schulze, Gawel, Nolzen, Weise, & Frank, 2016). Este facto prende -se quer pela incerteza associada à volatilidade dos preços, rendimentos incertos e custos de produção, quer pelo longo período de afectação dos solos que inviabiliza os processos de adaptação às dinâmicas dos mercados (Schulze et al, 2016).…”
Section: Conceitos Básicosunclassified